انعكاس ضعف الشرعية على عملية بناء النظام السياسي في ليبيا بعد 2011 - أبوزوية, فاطمة مصطفي; محمد, أماني عبدالرزاق (مجلة الاصالة, 2025)
انعكاس ضعف الشرعية على عملية بناء النظام السياسي في ليبيا بعد 2011